2007
DOI: 10.1152/japplphysiol.00434.2007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves glucose homeostasis that has been impaired by a high-fat diet by potentiating pancreatic β-cell function and mass through IRS2 in diabetic rats

Abstract: In this study, we investigated the effects of a high-fat diet and exercise on pancreatic beta-cell function and mass and its molecular mechanism in 90% pancreatectomized male rats. The pancreatectomized diabetic rats were given control diets (20% energy) or a high-fat (HF) diet (45% energy) for 12 wk. Half of each group was given regular exercise on an uphill treadmill at 20 m/min for 30 min 5 days/wk. HF diet lowered first-phase insulin secretion with glucose loading, whereas exercise training reversed this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 37 publications
(78 reference statements)
4
79
3
2
Order By: Relevance
“…Choi and colleagues reported that training enhanced beta cell proliferation and mass in 90% Px rats [11]. This finding was supported by Park et al, who demonstrated that training prevented the decline in first-phase insulin secretion in perfused islets and increased beta cell mass (via increased proliferation and reduced apoptosis) from high-fatfed 90% Px rats [12]. The increase in insulin-positive cells measured by immunohistochemistry reported across these studies varied from 20 to 50%.…”
Section: Search Strategymentioning
confidence: 72%
See 1 more Smart Citation
“…Choi and colleagues reported that training enhanced beta cell proliferation and mass in 90% Px rats [11]. This finding was supported by Park et al, who demonstrated that training prevented the decline in first-phase insulin secretion in perfused islets and increased beta cell mass (via increased proliferation and reduced apoptosis) from high-fatfed 90% Px rats [12]. The increase in insulin-positive cells measured by immunohistochemistry reported across these studies varied from 20 to 50%.…”
Section: Search Strategymentioning
confidence: 72%
“…For example, GH increases beta cell proliferation in vitro [9] and protects beta cell lines against IL-1β-, IFN-γ-and TNF-α-induced apoptotic cell death [10]. Increased IGF-1 signalling is thought to play a role in the increase in beta cell mass seen with exercise in 90% pancreatectomised (Px) rats [11,12]. IL-6, which is increased during exercise and elicits the increased circulating levels of GLP-1 during exercise, has an indirect effects on beta cell proliferation via GLP-1 [13].…”
Section: Search Strategymentioning
confidence: 99%
“…In fact, although an increase in insulin resistance results in an increased mass of beta cells to secrete more insulin to compensate for insulin resistance (22)(23)(24), severe long-lasting insulin resistance is associated with reduced proliferation of beta cells. As a result, in response to long-term insulin resistance, levels of beta cell mass are not maintained for adequate secretion of insulin (25). If the capacity of insulin secretion is sufficient to compensate for insulin resistance, people with insulin resistance will not develop diabetes (22).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a Korean study showed that a significant proportion of patients with type 2 diabetes are not obese and their insulin levels are normal or below normal (30). These studies point out in general that the non-obese Asians secrete insufficient amounts of insulin during insulin resistance, leading ultimately to type 2 diabetes (25,28). In recent years, researchers have found 70 genetic variants with the risk for diabetes, but TCF7L2 is still identified as the most im-portant diabetes susceptibility gene, so that the gene has carriers and variants with the greatest risk of type 2 diabetes (21,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation